The number of specimens in a furnace affects the biaxial flexural strength of veneered zirconia specimens after sintering - Rippe, Marília Pivetta (2020)
This study evaluated the effect of the number of specimens in a furnace during the firing of porcelain-zirconia (Y-TZP) discs on their biaxial flexural strength. Eighty bilayer disc-shaped specimens (∅: 15mm; thickness: 1.2 mm, ISO 6872) of zirconia (Vita In-Ceram YZ Cubes/Vita) and porcelain (Vita VM9) ceramics, were prepared and divided into four groups (n = 20) according to the number of specimens in a furnace for each porcelain sintering: G1- one disc/20 sintering cycles.; G2–two discs/10 sintering cycles.; G5-five discs/4 sintering cycles; and G10–ten discs/2 sintering cycles. Then, the specimens were submitted to biaxial flexure testing (BFS) (1 mm/min, water). The data (MPa) were analyzed with Kruskal-Wallis test followed by the Dunn's post hoc analysis at a 95% level of confidence (α = 0.05). Kruskal-Wallis showed that the number of samples in the furnace affected flexural strength (p < 0.0001). The highest BFS was observed for the G5 (132.3 MPa)A, which was significantly higher than G1 (53.6 MPa)B. No significant difference was observed for the Weibull moduli and characteristic strength among the groups. In terms of flexural strength, approximately five specimens at a time can be placed in a furnace for sintering.